Trifolium kurdistanicum (Trifolieae, Fabaceae), a new species of Trifolium sect. Trifolium from Iran - Yousefi, Somayeh; Saeidi, Hojjatollah; Maroofi, Hosein; Assadi, Mostafa; Ghaderi, Hiva (Phytotaxa, 2017)
Trifolium kurdistanicum, a new species of Trifolium sect. Trifolium from Kurdistan Province, west of Iran is described. It grows at high altitude on subalpine regions with steep slopes and shallow soil. The new species is morphologically close to T. longidentatum and can be considered as a member of the subsect. Ochroleuca. Trifolium kurdistanicum is characterized by large, multiple and branched stems, less than half of the stipule length adnate to the petiole, inflorescences without bracts, calyx with 3-nerved lower and 1-nerved upper teeth and all slightly longer than the tube, calyx nearly half the length of corolla, flowers violet or rarely white and seeds reniform.